Roman funerary monuments of south-western Pannonia in their material, social, and religious context - Migotti, Branka (Archaeopress Roman archaeology ;, 2018)
This book examines around 200 funerary monuments and fragments (stelai, sarcophagi, ash-chests, tituli, altars, medallions and buildings) from three Roman cities in the south-west part of the Roman province of Pannonia in the territory of north-west Croatia: colonia Siscia (Sisak) and municipia Andautonia (Sčitarjevo) and Aquae Balissae (Daruvar).